Standardization of back-table technique for uterus transplantation - Tamate, Masato; Testa, Giuliano; Bayer, Johanna; Johannesson, Liza (Fertility and sterility, 2025)
To present a standardized back-table technique for uterus transplantation (UTx). Step-by-step description of surgical technique and live-action narrated surgical footage showing back-table technique in UTx. Uterus transplantation has become a viable option for patients with absolute uterine factor infertility and their families. After performing 20 research cases, our institution has conducted UTx in 13 patients, and over 100 cases have been performed worldwide. Uterus transplantation is now considered technically feasible, with a high live birth rate after successful graft survival. The transplantation of a uterus involves three separate surgical components: living or deceased uterus retrieval; back-table preparation of the uterine graft; and implantation of the uterine graft in the recipient. The living donor hysterectomy and implantation of the uterus in the recipient can be seen in separate videos. The back-table process is critically important in transplant surgery. After the uterus is removed from the donor, organ perfusion, vascular preparation, and marking are essential for ensuring a smooth transition to recipient surgery. In this video, we demonstrate our standardized back-table technique. Currently, there are no articles in gynecology focused solely on back-table techniques. When selecting a potential donor, factors such as age, body mass index, general health, and obstetric and surgical history are considered. Once a candidate is deemed suitable, in-person screening includes blood tests, imaging studies, and mental health evaluations. Preoperative imaging provides valuable information on the condition of the uterine vascularity, which is crucial given the complexity and variability of pelvic vessels. Once the uterus is removed from a living or deceased donor, it is immediately placed on ice and flushed with cool preservation fluid on the back-table. Back-table procedures average 0.5–1 hours and includes the following: perfusion; preparation of the arteries; preparation of the veins; ligation of the base of the fallopian tubes; and four-point suturing of the vagina, as well as (optional) cervical cerclage. Preparing the veins is a key part of the back-table process, especially when the vessel diameters are small, necessitating conjoining. Additionally, because the uterus is a mobile organ located between the bladder and rectum, it is essential to assess the shape and positioning of the vessels that will be anastomosed to avoid torsion during the uterine-vessel anastomosis. We believe that our method will be useful for many institutions that wish to initiate UTx programs. Uterine graft viability and recipient pregnancy outcome. No surgical complications occurred. The postoperative course was uneventful, with early mobilization. The length of hospital stay was 5 days. The uterus was successfully implanted with successful pregnancy outcome. Our standardized back-table technique minimizes harm to the recipient. Furthermore, the technique does not compromise the uterine graft function. Further studies and more educational content using video will be key to the widespread adoption of uterine transplantation. Estandarización de la técnica de mesa auxiliar para el trasplante de útero Presentar una técnica estandarizada de mesa auxiliar para el trasplante de útero (UTx). Descripción paso a paso de la técnica e imágenes quirúrgicas narradas en directo que muestran la técnica de mesa auxiliar en el UTx. El trasplante de útero se ha convertido en una opción viable para pacientes con infertilidad absoluta por factor uterino y sus familias. Tras realizar 20 casos de investigación, nuestra institución ha llevado a cabo UTx en 13 pacientes, y se han realizado más de 100 casos en todo el mundo. El trasplante de útero se considera ahora técnicamente viable, con una elevada tasa de nacidos vivos tras la supervivencia satisfactoria del injerto. El trasplante de útero consta de tres componentes quirúrgicos independientes: extracción del útero de una donante viva o fallecida, preparación del injerto uterino e implantación del injerto uterino en la receptora. La histerectomía de la donante viva y la implantación del útero en la receptora pueden verse en vídeos separados. El proceso de la mesa auxiliar es de vital importancia en la cirugía de trasplante. Una vez extraído el útero de la donante, la perfusión del órgano, la preparación vascular y los reparos son esenciales para garantizar una transición fluida a la cirugía de la receptora. En este vídeo, mostramos nuestra técnica estandarizada de mesa auxiliar. En la actualidad, no existen artículos en ginecología centrados exclusivamente en las técnicas de mesa auxiliar. Al seleccionar a una posible donante, se tienen en cuenta factores como la edad, el índice de masa corporal, el estado general de salud y los antecedentes obstétricos y quirúrgicos. Una vez que se considera que una candidata es apta, la selección en persona incluye análisis de sangre, estudios de imagen y evaluaciones de salud mental. La imagenología preoperatoria proporciona información valiosa sobre el estado de la vascularización uterina, que es crucial dada la complejidad y variabilidad de los vasos pélvicos. Una vez extraído el útero de una donante viva o fallecida, se coloca inmediatamente en hielo y se lava con líquido de conservación frío en la mesa auxiliar. Los procedimientos de mesa auxiliar duran entre 0,5 y 1 horas e incluyen lo siguiente: perfusión; preparación de las arterias; preparación de las venas; ligadura de la base de las trompas de Falopio; y sutura de cuatro puntos de la vagina, así como cerclaje cervical (opcional). La preparación de las venas es una parte clave del proceso de la mesa auxiliar, especialmente cuando los diámetros de los vasos son pequeños y es necesario unirlos. Además, dado que el útero es un órgano móvil situado entre la vejiga y el recto, es esencial evaluar la forma y la posición de los vasos que serán anastomosados para evitar la torsión durante la anastomosis útero-vaso. Creemos que nuestro método será útil para muchas instituciones que deseen iniciar programas de UTx. Viabilidad del injerto uterino y resultado del embarazo de la receptora. No hubo complicaciones quirúrgicas. El postoperatorio transcurrió sin complicaciones, con movilización temprana. La estancia hospitalaria fue de 5 días. El útero se implantó con éxito con un resultado de embarazo satisfactorio. Nuestra técnica estandarizada de mesa auxiliar minimiza el daño a la receptora. Además, la técnica no compromete la función del injerto uterino. La realización de más estudios y el contenido educacional videográfico serán clave para la adopción generalizada del trasplante uterino.